POLITICAL RUMORING ON TWITTER DURING THE 2012 US PRESIDENTIAL ELECTION: AN EXPLORATORY STUDY - Shin, Jieun; Jian, Lian; Driscoll, Kevin; Bar, François (AoIR Selected Papers of Internet Research, 2015)
As much as Twitter played a major role in political discourse during the 2012 US presidential election, it also served as a conduit for unsubstantiated rumors and misinformation. Based on large-scale content analyzed Twitter messages (n=330,538), our exploratory analyses reveal that rumors about presidential candidates were mainly spread through a retweet button, yet hardly contested and corrected in a interactive process. Twitter showed a strong partisan structure for active rumor spreaders. However, rumor debunkers neither formed a cohesive community, nor exhibited a partisan structure. We found mixed results for the effects of rumor debunking effort. Professional rumor debunking sites (e.g., Factcheck.org) were relatively effective in curbing spread of satire-based rumors, but did not show significant influence on other types of rumors. Implications for the affordances of Twitter and effective rumor debunking strategies are discussed.